Nineteenth century connections between capitalism and colonialism in Antarctica: The case of sealing in the South Shetlands - Cruz, María Jimena (2024)
This chapter offers a reflection on colonialism and Antarctic sealing, considering how sealing may have shaped (or been shaped by) specific colonial dynamics. In particular, we discuss how colonialism and capitalism may have been complementary and indeed mutually reinforcing. By bringing colonialism into sealing, we offer an alternative understanding of an industry that has beenapproached primarily from a capitalist perspective. Drawing on insights from post-colonial studies, we also discuss the presence of specific colonial practices and relations that animated the industry. We begin with an overview of the history of Antarctica, looking at the interactions that people have had with the territory over time. This is important in determining whether capitalist or colonial dynamics acquired greater relevance at different moments, leading scholars to approach different periods through the lens of capitalism or colonialism alone. Later, we present sometools for discussing colonialism and capitalism in the region, exploring how they may have worked together in the sealing era. Research from the ‘Landscapes in White’ project, to which the three authors belong, contributes to the analysis.